2017
DOI: 10.5812/traumamon.13573
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis of Mortalities Resulting from Car Accidents in the Injured Individuals Hospitalized in Shiraz Shahid Rajaee Hospital During 2010 - 2016

Abstract: Background: Traffic events are among the greatest health problems which are ignored among other health issues. The health damages and treatments related to these events can involve individuals for a long period of time.Objectives: Therefore, using time series analysis, this study aimed to predict the mortality resulting from car accidents in the injured individuals referring to Shiraz Shahid Rajaee hospital.Methods: This ecological study was conducted on all the patients hospitalized in Shahid Rajaee hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A significant relationship has been reported between road traffic accidents (RTA) and time (e.g., the time of the day) in Yazd, Iran, during the New Year holidays and sum- (21). The mortality rate due to traffic accidents is higher in Iran at midnight and summer (22,23) and in spring and summer in Shiraz (24) than in other times. The present study showed that the speeding rate was higher from midnight to early morning throughout Iran.…”
Section: Discussionmentioning
confidence: 85%
“…A significant relationship has been reported between road traffic accidents (RTA) and time (e.g., the time of the day) in Yazd, Iran, during the New Year holidays and sum- (21). The mortality rate due to traffic accidents is higher in Iran at midnight and summer (22,23) and in spring and summer in Shiraz (24) than in other times. The present study showed that the speeding rate was higher from midnight to early morning throughout Iran.…”
Section: Discussionmentioning
confidence: 85%
“…Applications of time series analysis in road traff c mortality and serious injuries are reported in [8], [9], [10], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a review of the literature, there is no study that have analyzed traffic accidents in Iran and predicted its trend by 2021. It is of utmost importance to prevent traffic accidents, as it helps to avoid the imposition of costs and the associated adverse effects [10]. In order to implement prevention policies, it is essential to exactly identify the factors and assess the effects of the implementation of the solutions.…”
Section: Introductionmentioning
confidence: 99%